Financial consumer protection and its application in Takaful operations in Malaysia - Nur I'ffah Muhammad Nasir (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2021)
This study investigated the financial consumer protection mechanism within takaful operations in Malaysia and the ways it could be improved to better protect the financial consumers. The scope of this study is confined to unsuitable products and unfair treatment risks according to the categorization of risks in consumer protection by Nienhaus (2016). International standards on financial consumer protection were reviewed to formulate the themes of the study. The financial consumer protection principles were also extracted from the two main sources of Shariah: namely Quran and Sunnah. They were scrutinized to determine which principles apply to this study based on comparison with the findings obtained from the study. Semi-structured interviews were conducted to gain insight into the practice of financial consumer protection throughout the takaful operations in Malaysia. The insight from the interview was further complemented with the analysis of relevant documents. The findings of the study were derived from the data collection indicated that the regulatory landscape of Islamic finance in Malaysia is prudently regulated by Bank Negara Malaysia (BNM), covering aspects such as disclosure and transparency, fair treatment, and business conduct, as well as complaints handling and redress mechanism. Financial awareness and understanding which complement financial consumer protection initiatives in improving the efficiency, transparency, competition as well as access to the retail financial market was also found in the study. The study acknowledged tremendous effort that has been made for the protection of the financial consumers. However, looking at the low level of financial awareness and understanding of the consumers or takaful participants, there is room for TOs to further improve their financial consumer protection mechanism. The study also highlighted on TOs’ role in elevating the level of financial awareness and understanding among consumers in Malaysia. Lastly, the study proposed practical recommendations for the improvement of financial consumer protection mechanism for the takaful industry in Malaysia.